2019
DOI: 10.1002/ldr.3398
|View full text |Cite
|
Sign up to set email alerts
|

Flood‐induced metal contamination in the topsoil of floodplain agricultural soils: A case‐study in Colombia

Abstract: Anomalously cold conditions in the tropical Pacific, related to a strong La Niña event, affected numerous countries in 2010. Several areas in Colombia were severely impacted, including agricultural fields in La Mojana floodplain that were completely flooded for almost 2 years. This study assesses the effects of flooding on the levels, spatial distribution, and sources of trace metals in 222 agricultural topsoils of this floodplain. Our results show that mean concentrations of Cu 48.4 mg kg −1 (11-103 mg kg −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
(65 reference statements)
0
11
0
6
Order By: Relevance
“…Subregion 3 has intermediate precipitations (1500 mm yr −1 ≤ precipitation ≤ 2500 mm yr −1 ) with moderate coefficients of variation; however, in the vicinity of the Ciénaga de Chilloa (south of the department, see Figure 1), high variability was evidenced. This waterbody is located in the south of the department and receives the influence of the La Mojana region, an alluvial delta and a wetlands system characterized by high precipitation, covering 5500 km 2 [61]. Finally, Subregion 4 extends on the coastal zone of the department and shows a low-rainfall latitudinal gradient that decreases with the proximity to the sea (<1000 mm yr −1 ); this is mainly explained by the presence of dry and warm katabatic winds.…”
Section: Resultsmentioning
confidence: 99%
“…Subregion 3 has intermediate precipitations (1500 mm yr −1 ≤ precipitation ≤ 2500 mm yr −1 ) with moderate coefficients of variation; however, in the vicinity of the Ciénaga de Chilloa (south of the department, see Figure 1), high variability was evidenced. This waterbody is located in the south of the department and receives the influence of the La Mojana region, an alluvial delta and a wetlands system characterized by high precipitation, covering 5500 km 2 [61]. Finally, Subregion 4 extends on the coastal zone of the department and shows a low-rainfall latitudinal gradient that decreases with the proximity to the sea (<1000 mm yr −1 ); this is mainly explained by the presence of dry and warm katabatic winds.…”
Section: Resultsmentioning
confidence: 99%
“…Integrated palm-cattle systems, where cattle graze under trees or are fed palm fronds removed as part of plantation maintenance, would also be impacted. Increases in the frequency, duration and intensity of heavy rainfall events, drought periods and sea level rise will also increase exposure of water, croplands and grasslands to soil contaminants with potential harmful impacts for crop and forage yield quantity and quality ( Biswas et al, 2018 ; Lemonte et al, 2017 ; Marrugo-Negrete et al, 2019 ).…”
Section: Exposure Of Human and Natural Systemsmentioning
confidence: 99%
“…Goldmine was commonly associated with lead‐bearing ore. Pb entered into the soils through the dust and waste residue produced in the process of gold mining. The work of Marrugo‐Negrete, Pinedo‐Hernández, Combatt, Bravo, and Díez (2019) in Colombia revealed that Pb was the most polluted element in gold mining region. In conclusion, F3 comes from industrial, mining pollution, and traffic emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Bravo, and Díez (2019) in Colombia revealed that Pb was the most polluted element in gold mining region. In conclusion, F3 comes from industrial, mining pollution, and traffic emissions.…”
mentioning
confidence: 99%